Cardiac output and cardiac index measured with cardiovascular magnetic resonance in healthy subjects, elite athletes and patients with congestive heart failure - Carlsson Marcus; Andersson Ruslana; Bloch Karin; Steding-Ehrenborg Katarina; Mosén Henrik; Stahlberg Freddy; Ekmehag Bjorn; Arheden Hakan (Journal of Cardiovascular Magnetic Resonance, 2012)
Abstract Background Cardiovascular Magnetic Resonance (CMR) enables non-invasive quantification of cardiac output (CO) and thereby cardiac index (CI, CO indexed to body surface area). The aim of this study was to establish if CI decreases with age and compare the values to CI for athletes and for patients with congestive heart failure (CHF). Methods CI was measured in 144 healthy volunteers (39 ± 16 years, range 21–81 years, 68 females), in 60 athletes (29 ± 6 years, 30 females) and in 157 CHF patients with ejection fraction (EF) below 40% (60 ± 13 years, 33 females). CI was calculated using aortic flow by velocity-encoded CMR and is presented as mean ± SD. Flow was validated in vitro using a flow phantom and in 25 subjects with aorta and pulmonary flow measurements. Results There was a slight decrease of CI with age in healthy subjects (8 ml/min/m2 per year, r2 = 0.07, p = 0.001). CI in males (3.2 ± 0.5 l/min/m2) and females (3.1 ± 0.4 l/min/m2) did not differ (p = 0.64). The mean ± SD of CI in healthy subjects in the age range of 20–29 was 3.3 ± 0.4 l/min/m2, in 30–39 years 3.3 ± 0.5 l/min/m2, in 40–49 years 3.1 ± 0.5 l/min/m2, 50–59 years 3.0 ± 0.4 l/min/m2 and >60 years 3.0 ± 0.4 l/min/m2. There was no difference in CI between athletes and age-controlled healthy subjects but HR was lower and indexed SV higher in athletes. CI in CHF patients (2.3 ± 0.6 l/min/m2) was lower compared to the healthy population (p < 0.001). There was a weak correlation between CI and EF in CHF patients (r2 = 0.07, p < 0.001) but CI did not differ between patients with NYHA-classes I-II compared to III-IV (n = 97, p = 0.16) or patients with or without hospitalization in the previous year (n = 100, p = 0.72). In vitro phantom validation showed low bias (−0.8 ± 19.8 ml/s) and in vivo validation in 25 subjects also showed low bias (0.26 ± 0.61 l/min, QP/QS 1.04 ± 0.09) between pulmonary and aortic flow. Conclusions CI decreases in healthy subjects with age but does not differ between males and females. We found no difference in CI between athletes and healthy subjects at rest but CI was lower in patients with congestive heart failure. The presented values can be used as reference values for flow velocity mapping CMR.